Perancangan Arsitektur Enterprise Teknologi Informasi Menggunakan Metode TOGAF ADM (Studi Kasus : SMK Negeri 1 Manokwari) - Yodhy Yabes Yulezar Turukay; Alex De Kweldju; Lorna Yertas Baisa (G-Tech: Jurnal Teknologi Terapan, 2024)
SMK Negeri 1 Manokwari is public vocational school situated in Manokwari, West Papua. Currently, the school lacks an integrated information systems and information technology (IS/IT) infrastructure to facilitate its operational processes, such as student enrollment, employee data management, and financial transactions, all of which are presently handled manually. This study aims to devise an enterprise architecture tailored to the information and communication technology needs of the school. The enterprise information technology architecture design will be crafted utilizing the TOGAF (The Open Group Architecture Framework), adhering to the initial five stages of the TOGAF ADM (Architecture Development Method): Preliminary, Architecture Vision, Business Architecture, Application & Data Architecture, and Technology Architecture, specifically tailored for SMK Negeri 1 Manokwari.This research yields portfolio of applications: SIPS, SIK, and SIKU. The objective is to improve service delivery according to requirements, thereby enhancing the overall service quality to support the business processes at SMK Negeri 1 Manokwari.